Association of STAT4 rs7574865 with sysceptibility to juvenile onset systemic lupus erythematous in Pakistani population - Bashir, Rasheeda; Ali, Hira; Malik, Saira; Munir, Neelma; Haq, Rukhama; Naz, Shagufta; Imran, Altaf (Penerbit Universiti Kebangsaan Malaysia, 2020)
Association of STAT4 (signal transducer and activator of transcription4) haplotype tagged by single nucleotide polymorphism (SNP) rs7574865 with systemic lupus erythematosus (SLE) was reported in different populations. This study was aimed to investigate a genetic association between STAT4 single nucleotide polymorphism (rs7574865) with susceptibility and clinical features of systemic lupus erythematosus in Pakistani population. A total of 75 clinically diagnosed individuals affected with SLE were enrolled from Children’s Hospital and Institute of Child Health Lahore. Sixty-eight healthy individuals of same ethnicity were also enrolled for this study. Clinical assessment of patients was done with the help of clinical features suggestive for SLE and some diagnostic tests specific for the disease were performed. SNP rs7574865 was genotyped by allele specific tetra ARMS PCR assay to check and compare the genotypic allele frequencies between SLE patients and healthy controls. Different statistical analysis ChiSquare, Fisher’s exact tests and binary Logistic Regression is performed to determine association of risk alleles with SLE in Pakistani population. p value less than >0.05 consider significant. This study showed the frequency of GG (28%), TT (12%), and GT alleles (60%) in SLE patients while controls showed allele frequencies of GG (5%), TT (29%) and GT (64%), respectively. The results showed that GG genotype and G allele in STAT4 rs7574865 was the risk allele for SLE while T allele proved to be the protective one for disease susceptibility when compared with healthy controls genotypic frequencies. This study suggests the strong association of SNP rs7574865 in STAT4 with the risk of SLE in Pakistani population. However, G allele showed no association with organ damage and immune disorder of SLE.